Development and validation of an ultra-high performance liquid chromatography photodiode array method for the quantification of donepezil in human plasma and its application - Boonprasert R. (2023)
An ultra-high performance liquid chromatography-photodiode array detection (UHPLC-PDA) method was developed and validated for determination of the concentration of donepezil in patient’s plasma. Plasma spiked with diphenhydramine as an internal standard was used for the solid phase extraction. The eluent solution was diluted with 0.05% trifluoroacetic acid and injected into an UHPLC system. Chromatographic separation was performed on a reverse phase column (1.8 μm, 100 mm x 2.1 mm I.D.) and using acetonitrile with 0.05% trifluoroacetic acid in milli-Q water as the mobile phase. The gradient program for the mobile phase involved a flow rate of 0.45 mL/min and 3 min total run time. The photodiode array (PDA) detector was chosen to operate at 230 nm. The retention times were 1.70 and 2.11 min for donepezil and diphenhydramine, respectively. The method was developed and fully validated according to United Stated Food and Drug Administration (USFDA) guidance. The linearity of the method revealed a coefficient of determination or square of r greater than 0.998 in the concentration range 10-250 ng/mL. Extraction recoveries ranged from 84.6-85.6% with good repeatability. A simple, rapid, and reproducible UHPLC/PDA method for quantifying the concentration of donepezil in patient’s plasma was thus developed and completely validated. This method was successfully utilized to measure the plasma concentration of 105 Thai patients with Alzheimer’s disease and vascular dementia.